1980
DOI: 10.1017/s0074180900036597
|View full text |Cite
|
Sign up to set email alerts
|

The S. F. Smerd Memorial Lecture: The Sun of Stefan Smerd

Abstract: This lecture commemorates the memory, so recent, of our esteemed and much-loved colleague, Steve Smerd, who died in Sydney a few days before Christmas day last year. The fact that there was a spontaneous move to pay our respects in this unusual way, dedicating an international scientific symposium to honour his memory, must mean that we are dealing with a special individual as a scientist. What do we remember about Steve, the scientist, that was special? I do not think it will be es pecially for his writings a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 7 publications
2
34
0
Order By: Relevance
“…(Kundu 1965). Bremsstrahlung radiation originates from freefree emission through Coulomb collisions between electrons and ions (Wild et al 1963). The emission flux from bremsstrahlung is also dependent on the plasma EM, similarly to the EUV emission.…”
Section: Introductionmentioning
confidence: 99%
“…(Kundu 1965). Bremsstrahlung radiation originates from freefree emission through Coulomb collisions between electrons and ions (Wild et al 1963). The emission flux from bremsstrahlung is also dependent on the plasma EM, similarly to the EUV emission.…”
Section: Introductionmentioning
confidence: 99%
“…The speed V II with which the Type II source moves through the corona is observed to be of order 10 3 km/sec (Wild et al 1963). The empirical values of V II are considerably larger than the isothermal speed of sound V s in the coronal protons: at temperatures which are typical of the solar corona, i.e.…”
Section: Type II Radio Bursts and The Alfven Speedmentioning
confidence: 86%
“…At the time of the Wild et al (1963) paper, reliable observational information about the physical parameters of CME's was lacking: spacecraft images of CMEs did not become available until the early 1970's (Tousey 1973;MacQueen et al 1974). As a result, the relationship between Type II bursts and CME's (the principal topic of the present paper) could not be addressed by Wild et al (1963).…”
Section: Type II Radio Bursts and The Alfven Speedmentioning
confidence: 91%
See 1 more Smart Citation
“…From the solar burst point of view, type III solar bursts are the most common types of bursts received by the solar corona associated with the solar flares which are characterized by a rapid drift from high to low frequency which is attributed to the decreasing electron plasma frequency fp encountered by the fast particles as they moved outward from the solar corona (Lin, 1981). These bursts were first discovered in the frequency range 500 to 10 MHz [7] and then at lower frequencies using space radio instruments [8]. It was recently shown that a specific class of flares or Coronal Mass Ejections (CMEs) events associated with flare-generated shock waves exists For what appears on the surface to be an exotic mechanism, plasma emission is remarkably prevalent in the solar atmosphere, appearing in some form in quite a large fraction of flares [9] (Benz, 2005).This paper updates the largest solar flare that occurred on 9 th March 2012 and successfully detected in National Space Centre, Banting, Malaysia [10].…”
Section: Introductionmentioning
confidence: 99%